Kualitas Pelayanan Administrasi Akademik dan Resistensi Mahasiswa Program Studi Teknik Komputer Kontrol Politeknik Madiun - Susanto, Fredy (Jurnal Varidika: Varia Pendidikan, 2014)
The purposes of this study are: (1) to determine the characteristics of academic administrative (2) to know the description of academic and administrative services and the student resistances. The study is a descriptive qualitative. It is conducted at the Computer Control Engineering Program of Polytechnic Madiun. The respondents in this study are the Chairman, staff, and students of Computer Control Engineering Program. The main data collection tools by means of interviews and documentation. It was developed by the researcher himself and validity tested by triangulation techniques. The results of this study concluded: 1) control program engineering studies led by the chief together with the secretary program, and assisted by the administrative staff. The academic administrations are student planning card, attendance list, class scheduling, semester reporting, the final semester result reporting, and final project schedule, 2) generally the academic administrative services do not fulfill the students satisfactory, such as administrative room less extensive, administrative officer less responsive in providing some services and not in line with a predetermined schedule, but the level of student resistance remains high.